Environmental Culture and the Factors Affecting It (Case Study: The Citizens of Shiraz City) - Zahra Hemmati; S. Mohammad Shobeiri (Taḥqīqāt-i Farhangī-i Īrān)
In recent years, the environmental crisis is considered as one of the major challenges that human is faced. Many scientists have proposed technological solutions to reduce or prevent environmental crises, however, some of them have suggested the necessity of new relation and interaction between nature and human, and also, the need for a new environmental culture. This study aims to explore the environmental culture and its influencing factors in Shiraz city. Research was conducted by using survey method, cluster sampling and questionnaire. In total, 402 completed questionnaires were collected and analyzed. Research findings indicate that environmental culture had positive and significant relationship with opportunities and facilities offered, feeling efficiency and environmental education. However, environmental culture had no significant relationship with environmental knowledge and social norms. Also, multivariate regression results show that opportunities and facilities offered and feeling efficiency are significant with environmental culture.